Literatur Review: Implementasi Manajemen Keluarga dalam Pertumbuhan Kecerdasan Emosi dan Komunikasi Anak - Trisnani Widowati; Mia Hafizah Tumangger; Kartika Dwi Hapsari; Itsnayni, Itsnayni; Wanda Febi Safira; Mutiara Nur Marina; Varisa Berliana Al-Azhar (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Family management plays a pivotal role in establishing equilibrium between emotional dynamics and communication among family members. The family environment constitutes the primary context in which children learn to interact, communicate, and develop their character. Parental communication patterns, along with their capacity for emotional regulation, serve as critical determinants of a supportive home atmosphere conducive to children’s developmental and educational outcomes. This study aims to examine the influence of communication management and emotional management within the family on the development of children’s emotional intelligence and their overall academic success. This research employs a literature review approach by critically analyzing various sources, including scholarly journals, books, and relevant empirical studies. The findings indicate that effective communication management characterized by openness, empathy, and mutual respect strengthens parent child emotional bonds, enhances learning motivation, and improves academic achievement. Furthermore, sound emotional management enables parents to regulate stress and model appropriate self-control, thereby fostering a harmonious and productive learning environment within the household.